2008
DOI: 10.1021/om701275u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of 9-Nickelafluorenyllithium Complexes

Abstract: 1), was prepared in the reaction between 2,2′dilithiobiphenyl and nickelocene in diethyl ether. Compound 1 was transformed to other 9-nickelafluorenyllithium compounds, 2) and (η 5 -(1-(η 5 -cyclopentadienyl))-1nickelafluorenyl)lithium(dimethoxyethane) (3), whose crystal and molecular structures were determined by single-crystal X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…We have found that the ground state of 9-nickelafluorenide complex has spin multiplicity of 1, which is in good agreement with experimental results [1]. Triplet state lies 105 kJ/mol above singlet.…”
Section: Dft Calculationssupporting
confidence: 90%
See 2 more Smart Citations
“…We have found that the ground state of 9-nickelafluorenide complex has spin multiplicity of 1, which is in good agreement with experimental results [1]. Triplet state lies 105 kJ/mol above singlet.…”
Section: Dft Calculationssupporting
confidence: 90%
“…We have reported the synthesis of 9-nickelafluorenyllithium complexes [1], novel metallafluorenyl-alkali metal compounds that contain a transition metal in the five-membered metallacyclic ring. Such compounds proved to be very useful in the synthesis of metallametalocenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination of DME to the Li cation generates the free anionic [NiCp(2,2 -bph)] − complex (31) (Fig. 17) [27].…”
Section: Synthesis By Transmetallationmentioning
confidence: 99%
“…the now popular 2-phenylpyridine complexes mentioned in the Introduction [3,4]. Rillema and co-workers have extensively studied the absorption and emission properties of a number of Pt(2,2 -bph) complexes with the mono-and bidentate ligands, pyridine, acetonitrile, ethylenediamine, CO (27) [23,42], dppm [44,45], and the bridging ligand SEt 2 [41]. Absorption spectra of mono-metallic [Pt(2,2 -bph)(py) 2 ] (52), [Pt(2,2 -bph)(NCMe) 2 ] bonyl complex 27 have been carried out to examine singlet and triplet excited states, and to compare calculated geometries with those from the X-ray crystallographic data previously obtained [42,43].…”
Section: Luminescent Transition Metal 22 -Biphenyl Complexesmentioning
confidence: 99%